Effect of Multiple Chronic Diseases on Health Care Expenditures in Childhood - Wenjun Zhong; Dawn M. Finnie; Nilay D. Shah; Amy E. Wagie; Jennifer L. St. Sauver; Debra J. Jacobson; James M. Naessens (SAGE Publishing, 2015)
Objectives: To examine multiple chronic conditions and related health care expenditures in children. Methods: Retrospective cohort study of all dependents of Mayo Clinic employees aged 0-17 on Jan 1, 2004 with continuous health benefits coverage for 4 years (N=14,727). Chronic conditions, health care utilization, and associated expenditures were obtained from medical and pharmacy claims. Results: The most prevalent chronic conditions were asthma/chronic obstructive pulmonary disease (12%), allergic rhinitis (11%), and behavior problems (9%). The most costly conditions were congenital anomalies, asthma/chronic obstructive pulmonary disease, and behavior problems ($9602, $4335, and $5378 annual cost per child, respectively). Annual health care expenditures increased substantially with the number of chronic conditions, and a small proportion of children with multiple chronic conditions accounted for a large proportion of health care costs. In addition, those with multiple chronic conditions were more likely to persist in the top 10th percentile spender group in year-to-year spending. Conclusion: Children with multiple chronic conditions accounted for a large proportion of health care expenditures. These children were also likely to persist as high spenders in the 4-year time frame. Further research into effective ways to manage the health care delivery for children with multiple chronic conditions is needed.